Foreword - Gaupseth, Silje; Federhofer, Marie-Theres; Aspaas, Per Pippin (Wehrhahn Verlag, 2013)
“Travels in the North” is the title of a symposium that was hosted by the Centre franco-norvégien en sciences sociales et humaines, in Paris, 5–6 October 2011. The Centre is owned by the Norwegian Universities of Oslo, Bergen, Trondheim, and Tromsø, and constitutes a part of the Fondation Maison des Sciences de l’Homme in Paris. The symposium took place in conjunction with the annual meeting of the board of the Centre.